2009
DOI: 10.1007/s11661-009-9917-y
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Electrical Resistivity, Particle Dissolution, Precipitation of Dispersoids, and Recrystallization Behavior of AA7020 Aluminum Alloy

Abstract: This research concerns the effect of homogenization treatment on the electrical resistivity of AA7020 aluminum alloy variants with different Zr and Cr contents. Small changes in the Zr and Cr contents of the as-cast alloy increase the electrical resistivity significantly. After employing various homogenization treatments, the electrical resistivity decreases, which is due to the depletion of Zr, Cr, and Mn in the matrix, by forming small dispersoids. The optimum treatment proposed in order to obtain the smalle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(26 citation statements)
references
References 34 publications
(98 reference statements)
2
24
0
Order By: Relevance
“…The possible reason for the change may due to the state of Zn atoms. According to Eivani et al [17], the thermal resistivity increment caused by the alloying element in Mg matrix is about one magnitude order larger than that in metallic compound, thus the slope of thermal conductivity tend to be larger in the alloys containing low Zn content than that with high concentration. In a recent research conducted by Pan et al [8] on the thermal conductivity of as-cast and as-solutionized binary Mg-Zn alloys with Zn content of 2-11 wt.%, the change of slope was also observed with the increasing of Zn content.…”
Section: Resultsmentioning
confidence: 99%
“…The possible reason for the change may due to the state of Zn atoms. According to Eivani et al [17], the thermal resistivity increment caused by the alloying element in Mg matrix is about one magnitude order larger than that in metallic compound, thus the slope of thermal conductivity tend to be larger in the alloys containing low Zn content than that with high concentration. In a recent research conducted by Pan et al [8] on the thermal conductivity of as-cast and as-solutionized binary Mg-Zn alloys with Zn content of 2-11 wt.%, the change of slope was also observed with the increasing of Zn content.…”
Section: Resultsmentioning
confidence: 99%
“…However, a large fraction of grains contained Cr below its nominal value. In particular, low Cr levels were [62][63][64] found near the grain boundaries and interdendritic regions. Therefore, it can be concluded that the reason for the small numbers of Cr-containing dispersoids in the grain boundary regions is the negligible concentrations of this element in these regions due to microsegregation during DC-casting.…”
Section: Comparison Between the Qxrd And Qsem Resultsmentioning
confidence: 99%
“…The intention of preparing this chapter is to investigate the microstructural evolution during homogenization and therefore, discussion on the effect of homogenization treatment on recrystallization inhibition has been avoided. For more details, the reader is referred to other references [3,63,64,68,69]. The number density of the Zr-containing dispersoids decreases significantly with increasing distance towards the grain boundaries.…”
Section: T S H O U L D B E M E N T I O N E D T H a T I N O R D E R mentioning
confidence: 99%
“…Regarding feret, (Figure 6b), the index is reduced appreciably at 2 h homogenization with a further slight reduction at 6 h homogenization. The intermediate slight increase of the feret index between 2 and 4 h homogenization is attributed to the protrusions formed at the particle surface, a process accompanying the pinching process, as suggested in [15,16]. The circularity index, (Figure 6c), exhibits a continuous reduction with homogenization time, with the largest reduction appearing after 2 h homogenization.…”
mentioning
confidence: 78%